The End of Scale - Maney, Kevin; Taneja, Hemant (MIT Sloan Management Review, 2018)
For more than a century, economies of scale made the corporation an ideal engine of business. However, the emergence of platforms and technologies that can be rented as needed have eroded the relationship between fixed costs and output that defined economies of scale. Together, these new factors have enabled small companies to pursue niche markets and successfully challenge large established companies that are weighed down by investments in mass production, distribution, and marketing. "Investments in scale used to make a lot of sense," argues author Hemant Taneja. They supported the development of cars, airplanes, radio, and television, and built out the electric grid and telephone system. But with the emergence of mobile, social, cloud computing, and artificial intelligence in recent years, Taneja argues that business logic has shifted toward what he describes as "the economics of unscale," which allows for mass customization for increasingly narrow markets. Because companies can stay nimble and focused by easily and instantly renting scale, they can adjust quickly to changing demand and conditions with little cost and relatively little effort. According to Taneja, large corporations are taking note. Traditionally, Procter & Gamble Co. invented most of its new products in-house. But in recent years it has started to tap into ideas from outside inventors who submit ideas via the internet. Other large companies, including General Electric Co. and Walmart Stores Inc., are tapping into new, unscaled businesses as well. Taneja presents three recommendations to large companies seeking to remain relevant. His first recommendation is to become a platform. Operating a platform can be enormously profitable because the companies that operate on the platforms come to depend on them for their success. The author's second recommendation is to instill a product focus. Big companies, he argues, get sidetracked on issues that have little to do with making great products. But in an unscaled era, this can create openings for focused small competitors. His third recommendation is to find growth opportunities through what he calls "dynamic rebundling." The winners in the unscaled economy, he writes, "make every customer feel like a market of one." Products and services that are tailored to individuals will often have an advantage over mass-market products and services, Taneja says. Corporations, therefore, can try to maintain their advantage with collections ...